Pendampingan UMKM Maju Digital Melalui Digital Marketing Bagi UMKM Desa Kemuningsari Lor, Kecamatan Panti, Jember - Zainul Hasan; Muhammad Yunus (Jurnal Pengabdian Literasi Digital Indonesia, 2022)
The rapid development of technology requires businesses to be able to adapt quickly. Through the use of technology in business, it can help Micro, Small and Medium Enterprises (MSME’s) or other businesses develop their businesses so that they are known by many people. One area that has problems with limited technology in marketing products is Kemuningsarilor Village, which is in Panti District, Jember Regency. Through the Collaborative KKN, the local regency government sent students from 13 universities throughout Jember to perform community service which is expected to overcome existing problems. The Collaborative KKN was held for 35 days, from 23 July 2022 to 26 August 2022. With the MSME Digital Marketing Creative Socialization program by the 153 Collaborative KKN participants, it can help existing MSMEs in developing product marketing. The activity went through three stages, namely the preparation process, the implementation process, and closing. From this activity, MSME’s have increased in terms of understanding, knowledge and awareness of MSME actors regarding the use of digital marketing strategies to expand product reach.